OP0123 In Human Chondrocytes DNMT-1 Plays a Key Role in the Expression of Several Genes Associated with the Pathogenesis of Osteoarthritis. (23rd January 2014) - Akhtar, N.; Haqqi, T. M.
Abstract : Background: Recent evidence points to chromatin remodeling as a key event in the expression of several genes associated with OA pathogenesis. IL-1β is the principal cytokine involved in cartilage catabolism in OA but whether it induces chromatin remodeling in chondrocytes is not known. Objectives: To investigate (a) whether IL-1β modulates DNA methylation content in human chondrocytes; (b) how the DNA methylation status affect the expression of selected downstream genes; and (c) whether the effect on DNA methylation is the same or different in chondrocytes from the superficial and deep zones of the human articular cartilage. Methods: Femoral head cartilage samples (n=12) obtained at the time of hip arthroplasty were stained with India ink and only the unaffected, smooth cartilage was used. A portion of the cartilage was fixed, decalcified and analyzed histologically. Chondrocytes were derived by enzymatic digestion of superficial zone (SZ) and deep zone (DZ) of the cartilage and cultured in monolayer. Chondrocytes stimulated with IL-1β (10ng/ml) in vitro for 24h were used in these studies. Gene expression of 84 human epigenetic modification enzymes was studied usinga PCR Array. Expression levels of DNMT-1, -3A, -3B, Thymine DNA glycosylase (TDG) and of selected genes was quantified by TaqMan Assays. Expression of Global DNA methylation level was determined using a Methylated DNA quantification kit. IL-1β-induced changes in the activity of DNMTs and DNA demethylases was studied using commercially available kits. Effect of DNA demethylation by 5-Aza-2 deoxycytidine (5-Aza) on the expression of MMPs, TIMPs, COX-2 and SOX-9 was also studied. SiRNA-mediated knockdown of DNMT-1 expression was used to study its role in the regulation of selected genes. Results were derived using Origin 6.1 software package and p<0.05 was considered significant. Results: Global DNA methylation increased in the DZ (128%) and SZ chondrocytes (44%) treated with IL-1b. Expression analysis of 84 genes known or predicted to modify genomic DNA and histones to regulate gene expression, identified 30 genes that displayed significant differences in expression upon IL-1β-stimulation. Results of both the mRNA array and TaqMan assays showed a significant up-regulation of DNMT-1, -3A and -3B gene expression upon IL-1β-stimulation which correlated with increased total DNMT and DNMT-1 enzyme activity in both the SZ and DZ chondrocytes. Interestingly, expression and activity of DNA demethylases and TDG enzymes was also increased in SZ chondrocytes by IL-1β-stimulation. Pharmacological DNA demethylation and knockdown of DNMT-1 resulted in significant increase in the expression of MMP-3, MMP-9, MMP-13, TIMP-2, and COX-2 and transcription factor SOX-9 in SZ chondrocytes. Conclusions: We identify for the first time several new candidate genes that show epigenetic regulation in response to IL-1β in human chondrocytes. We also show that IL-1β induce hypermethylation of genomic DNA in SZ and DZ chondrocytes, which positively correlated with the expression and activity of DNA methylatranferases. IL-1β stimulation also increased the expression and activity of DNA demethylasessuggesting a dynamic regulation of DNA methylation and demethylation in SZ chondrocytes. Our results also suggest a role of DNMT1 activity in mediating epigenetic modifications that regulate the expression of MMP-3, -9, -13, TIMP-2, SOX-9 and COX-2 in human chondrocytes. Acknowledgements: Supported by NIH grants AT 003627 and AT 005520. Disclosure of Interest: N. Akhtar: None Declared, T. Haqqi Grant/research support from: NIH